High Anodic-Voltage Focusing of Charge Carriers in Silicon Enables the Etching of Regularly-Arranged Submicrometer Pores at High Density and High Aspect-Ratio - Cozzi, Chiara; Polito, Giovanni; Strambini, Lucanos M.; Barillaro, Giuseppe (Frontiers in Chemistry, 2018)
The anodic dissolution of silicon in acidic electrolytes is a well-known technology enabling the silicon machining to be accurately controlled down to the micrometer scale in low-doped n-type silicon electrodes. Attempts to scale down this technology to the submicrometer scale has shown to be challenging, though it premises to enable the fabrication of meso and nanosystems that would greatly impact the fields of biosensors and nanomedicine. In this work, we report on the electrochemical etching at high anodic voltages (up to 40 V) of two-dimensional regular arrays of millions pores per square centimeter (up to 30 × 106 cm-2) with sub-micrometric diameter (down to ~850 nm), high depth (up to ~40 µm), and high aspect ratio (up to ~45) using n-type low-doped n-type silicon electrodes (resistivity 3-8 Ω cm). The use of high anodic voltages, which is over one order of magnitude higher than commonly used anodic voltage values, enable to tremendously improves hole focusing at the pore tips during the etching and, in turn, to control of electrochemical etching of submicrometer-sized pores when spatial period reduces below 2 μm. A theoretical model allows experimental results to be interpreted in terms of an electric-field-enhanced focusing of holes at the tip apex of the pores at high anodic voltages, with respect to the pore base, which leads to a smaller curvature radius of the tip apex and enables, in turn, the etching of pore tips to be preferentially sustained over time and space.